The directing effect of mono primary and secondary amine group substituted cyclotriphosphazenes on the reactions of the disodium salt of tetraethylene glycol - Balci, Ceylan Mutlu (Elsevier Science Sa, 2021)
This study examines how the mono primary and mono secondary amine groups on the cyclotriphosphazene ring will direct the tetraethylene glycol (a flexible diol) and which of the five active P-Cl bonds in the structure will be preferred in detail. Isopropylaminopentachlorocyclotriphosphazene (1a) and dimethylaminopentachlorocyclotriphosphazene (1b) were reacted with the disodium salt of tetraethylene glycol in THF solution at 1:1 mole ratio. Four new cyclotriphosphazene derivatives; 1,3-mono ansa (2a), mono spiro (3b), trans 3,5-mono ansa (4b) and cis 3,5-mono ansa (5b) were isolated. The structures of these compounds were characterized by elemental analysis, mass spectrometry (MALDI-TOF), 1H and 31P NMR spectroscopy. Additionally, the structure of compounds 2a, 4b and 5b were illuminated by single crystal X-Ray diffraction technique. In the reaction of compound 1a with the disodium salt of tetraethylene glycol, it was determined that the ONa+ group was primarily replaced the chlorine atom of the PCl(NHR) group (via proton abstraction/chloride elimination), whereas compound 1b gave a nucleophilic substitution reaction with chlorine atoms on other phosphorus atoms (via SN2 and SN1 reaction mechanisms, respectively).
Keywords: Cyclotriphosphazene; Directing effect; Regio isomer; Crystal structure